Perceived destination competitiveness of Langkawi Island: an evaluation / Zaliha Zainuddin, Salleh Mohd Radzi and Mohd Salehuddin Mohd Zahari. - Zainuddin, Zaliha; Mohd Radzi, Salleh; Mohd Zahari, Mohd Salehuddin (Universiti Teknologi MARA Cawangan Selangor, 2018)
Destination competitiveness has become a critical issue and creates increasingly challenging in tourism market. A successful tourism destination should embrace an integrated approach towards the many components of the tourism system and competitive advantage of a destination is closely relates to the quality of the products offered, which means the tourist satisfaction that experienced at the destination. This research note discussed the tourism destination competitiveness and highlight Langkawi Island as one of competitive tourism destination in Malaysia. These early finding indicated that the Key Success Factors and Perceived Destination Competitiveness are significant with experience investigate the travel revisit intentions to this destination.